A Novel Class Substituted Imidazo[2, 1‐b][1, 3, 4]thiadiazole Derivatives: Synthesis, Characterization, In Vitro Biological Activity, and Potential Inhibitors Design Studies. Issue 48 (20th December 2019) - Er, Mustafa; Ahmadov, Farid; Karakurt, Tuncay; Direkel, Şahin; Tahtaci, Hakan
Abstract: In this study, imidazo[2, 1‐ b ][1, 3, 4]thiadiazole derivatives were designed and synthesized. All of the synthesized compounds were characterized by 1 H and 13 C nuclear magnetic resonance ( 1 H NMR and 13 C NMR), fourier‐transform infrared spectroscopy (FT‐IR), elemental analysis, mass spectrometry, and X‐ray diffraction. The synthesized compounds were tested for antileishmanial activity against two Leishmania species and antibacterial activity against nine bacterial species in the study. It was observed that 2‐(4‐Fluorobenzylthio)‐6‐(4‐fluorophenyl)imidazo[2, 1‐ b ][1, 3, 4]thiadiazole (5 ) had the highest antileishmanial activity (MIC: 625 μg/mL). Also, 4‐(2‐(4‐fluorobenzylthio)imidazo[2, 1‐ b ][1, 3, 4]thiadiazol‐6‐yl)benzonitrile (10 ), 2‐(4‐fluorobenzylthio)‐6‐(4‐phenylphenyl)imidazo[2, 1‐ b ][1, 3, 4]thiadiazole (11 ), and 4‐(2‐(4‐methoxybenzyl)imidazo[2, 1‐ b ][1, 3, 4]thiadiazol‐6‐yl)benzonitrile (25 ) were found to be effective at different studied concentrations. PyRx software, which uses a Lamarckian genetics algorithm, was utilized to find the affinity values of all compounds in molecular docking simulations. Pharmacokinetic properties and toxicities of the ligands were then researched using PROTOX (a webserver for the prediction of oral toxicities of small molecules) and FAF‐Drugs (free adsorption distribution, metabolism, excretion (ADME) tox filtering tool). The study showed that the ligands had acceptable toxicity and ADME properties for the inhibition of the 3JUS receptor. Abstract : In the present work novel substituted imidazo[2, 1‐ b ][1, 3, 4]thiadiazole derivatives were synthesized starting from 2‐amino‐1, 3, 4‐thiadiazole. The synthesized compounds were evaluated for antileishmanial and antibacterial activities. According to the results of the biological activity tests, some of the synthesized compounds showed moderate to high levels of biological activity. The combination of experimental findings on SAR study and computational works revealed that the presence of electron withdrawing groups and less bulky groups on benzene ring have significant effects on the biological acitivities.